Corpus callosum volume in patients with first-episode psychosis - TOPUZOĞLU, AHMET (My University, 2022)
Objective In first-episode psychosis, a relationship may exist between disruption communication between two brain hemispheres and psychosis symptomatology. We aimed to investigate the relationship between corpus callosum (CC) volume and psychosis symptomatology in patients with first-episode psychosis. Methods This is a retrospective case-control study wherein first-episode psychosis cases and healthy controls were included from inpatient unit archives of the Department of Psychiatry and Department of Radiology, Dokuz Eylül University School of Medicine. Psychosis symptoms were assessed using the positive and negative syndrome scale (PANSS). The CC, the chief connection between two brain hemispheres, was examined using magnetic resonance imaging (MRI); 27 patients with first-episode psychosis and 29 healthy volunteers were evaluated via 1.5-T MR. MRI findings of CC volumes of the two groups were compared. Correlations between PANSS scores and CC volume were also evaluated. Results The CC volume was lower in patients with first-episode psychosis than in healthy controls. Moreover, we observed a significant negative correlation between the CC volume and emotional withdrawal scores, and a significant positive correlation between the CC volume and hallucinations. Conclusions The CC is a vital structure that connects two frontal lobes of the brain. There may be CC abnormalities in first-episode psychosis. Emotional withdrawal is associated with decreased CC volume, whereas hallucinations are associated with increased CC volume. The development of these symptoms may be associated with changes in CC connections.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); First-episode psychosis; corpus callosum; emotional withdrawal; hallucinations; WHITE-MATTER; SCHIZOPHRENIA; ABNORMALITIES; SIZE; METAANALYSIS; EPISODE